Structural and electrical characteristics of printed metal nanoparticle networks - Van den Berg, Claire Barbara (Department of Physics, 2017)
The structural and electrical properties of metal nanoparticle (NP) networks and their dependence on the constituent phases have been investigated. Percolation and effective media theories have been used to describe the physical properties of disordered systems, as well as providing a link between their structural features and the corresponding electrical transport properties. Silver and palladium nanoparticulate layers in ethyl cellulose polymer binder (ETHOCELTM), were fabricated onto paper using the method of screen printing. The metal-binder ratios were varied in order to observe changes in the microstructure when a percolating network consisting of the metal NPs is formed through the layer.